A multi-domain framework for modelling educational games: Towards the effective development in perspective of game environment - Ahmad, M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Game-based learning is one of the emerging industries of 21st century due to technological advancement and an ease of access to internet. Thus, developing an effective educational game which delivers concepts such as game play (rules and regulations), learning theories (theoretical based), subject-matter (learners and subject) and game environment is highly important. Furthermore, the collaboration between all the domains stated previously needs to be understood clearly by game developers in developing process. Therefore, this paper briefly highlights the proposed multi-domain framework for game developers to effectively model game and extracted implicit relationships based on game environment domain through a systematic literature review. This paper underlines sixteen (16) implicit relationships in perspective of game environment domain. They are validated through qualitative interviews with eight (8) game-based learning experts. Consequently, the results are interpreted in relevancy with all domains of framework by applying interpretive hermeneutic approach of qualitative study. The findings conclude 16 explicit relationships in perspective of game environment for game developers to guide them through development of educational games. Â© 2015 IEEE.